Cervical cancer screening for individuals at average risk: 2020 guideline update from the American Cancer Society. (30th July 2020) - Fontham, Elizabeth T. H.; Wolf, Andrew M. D.; Church, Timothy R.; Etzioni, Ruth; Flowers, Christopher R.; Herzig, Abbe; Guerra, Carmen E.; Oeffinger, Kevin C.; Shih, Ya‐Chen Tina; Walter, Louise C.; Kim, Jane J.; Andrews, Kimberly S.; et al.
Abstract: The American Cancer Society (ACS) recommends that individuals with a cervix initiate cervical cancer screening at age 25 years and undergo primary human papillomavirus (HPV) testing every 5 years through age 65 years (preferred); if primary HPV testing is not available, then individuals aged 25 to 65 years should be screened with cotesting (HPV testing in combination with cytology) every 5 years or cytology alone every 3 years (acceptable) ( strong recommendation ). The ACS recommends that individuals aged >65 years who have no history of cervical intraepithelial neoplasia grade 2 or more severe disease within the past 25 years, and who have documented adequate negative prior screening in the prior 10 years, discontinue all cervical cancer screening ( qualified recommendation ). These new screening recommendations differ in 4 important respects compared with the 2012 recommendations: 1) The preferred screening strategy is primary HPV testing every 5 years, with cotesting and cytology alone acceptable where access to US Food and Drug Administration‐approved primary HPV testing is not yet available; 2) the recommended age to start screening is 25 years rather than 21 years; 3) primary HPV testing, as well as cotesting or cytology alone when primary testing is not available, is recommended starting at age 25 years rather than age 30 years; and 4) the guideline is transitional, ie, options for screening with cotesting or cytology alone are provided but should be phased out once full access to primary HPV testing for cervical cancer screening is available without barriers. Evidence related to other relevant issues was reviewed, and no changes were made to recommendations for screening intervals, age or criteria for screening cessation, screening based on vaccination status, or screening after hysterectomy. Follow‐up for individuals who screen positive for HPV and/or cytology should be in accordance with the 2019 American Society for Colposcopy and Cervical Pathology risk‐based management consensus guidelines for abnormal cervical cancer screening tests and cancer precursors.